2015
DOI: 10.1242/jcs.174177
|View full text |Cite
|
Sign up to set email alerts
|

Promotion of periostin expression contributes to the migration of Schwann cells

Abstract: Neuregulin ligands and their ErbB receptors are important for the development of Schwann cells, the glial cells of the peripheral nervous system (PNS). ErbB3 deficiency is characterized by a complete loss of Schwann cells along axons of the peripheral nerves, impaired fasciculation and neuronal cell death. We performed comparative gene expression analysis of dorsal root ganglia (DRG) explant cultures from ErbB3-deficient and wild-type mice in order to identify genes that are involved in Schwann cell developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 59 publications
(74 reference statements)
2
22
0
Order By: Relevance
“…As a complementary approach, we sought to determine whether a HSC line can be induced to express POSTN. It has been reported that Neuregulin 1 (NRG1) and TGF-β can induce Postn expression in cultured rat Schwann cells (35). Further, Tgfb is highly expressed in the sciatic nerve of SAPP mice (Supplemental Figure 7), suggesting its presence at the site of inflammation.…”
Section: Resultsmentioning
confidence: 92%
See 3 more Smart Citations
“…As a complementary approach, we sought to determine whether a HSC line can be induced to express POSTN. It has been reported that Neuregulin 1 (NRG1) and TGF-β can induce Postn expression in cultured rat Schwann cells (35). Further, Tgfb is highly expressed in the sciatic nerve of SAPP mice (Supplemental Figure 7), suggesting its presence at the site of inflammation.…”
Section: Resultsmentioning
confidence: 92%
“…PNS autoimmunity in NOD.Aire GW/+ mice shares key features with human CIDP, including infiltration of peripheral nerves by CD4 + T cells and F4/80 + macrophages (25)(26)(27), IFN-γ production by CD4 + T cells (28,29), and peripheral nerve demyelination (7,30). We screened mRNA levels of 6 ECM genes with known roles in PNS development: laminin a2 (Lama2) (31), laminin a4 (Lama4) (31), laminin a5 (Lama5) (32), laminin b1 (Lamb1) (31), thrombospondin 2 (Thbs2) (33), and Postn (34,35). We used quantitative reverse transcription PCR (qRT-PCR) to compare the relative expression levels of these genes between sciatic nerves from age-matched WT (NOD.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We demonstrated that the competent human EGFR + SCp can be readily isolated from 365 differentiated hPSCs and form de novo myelination both in vitro and in vivo. The EGFR + cells 366 isolated from our in vitro system had unique gene expression profile including several genes and 367 pathways that have prominent roles in different steps of SC development and myelination 368 (Campana et al, 2003;Tawk et al, 2011) (Sonnenberg-Riethmacher et al, 2015. Importantly, 369 these cells are expandable and cryopreserved cells reserved their myelin forming ability when 370 co-cultured with peripheral neurons and in vivo.…”
Section: Discussion 359mentioning
confidence: 97%